Analyzing the attitudes of elite wrestlers related to the use of doping - Mine Koc; Mustafa Koc; Unal Turkcapar (Selcuk University, 2014)
Thepurpose of thisstudy is toanalyzetheattitudes of elite Turkishwrestlersrelatedtotheuse of doping. Thestudygroup of theresearchincludedfreestyleandGreco-Roman (cadet, junior,andsenior) 180 Turkishwrestlers in 2013 wrestling World Championship National Team trainingcamps. Inordertomeasuretheattitudes of wrestlers, "TheAttitudeScaleRelatedtotheUse of Doping" developedbyŞapcı (2010) (3), and "Personal Information Form" developedby us wereused. Accordingtotheresearchfindings, in thesub-dimension of theattitudescale, "I disapprovetrainers' encouragingtheathletesupontheuse of doping" had thelowestand "Use of doping causesunfaircompetitionamongtheathletes" had thehighestscore. Incomparisonsaccordingtothevariables, whereasnosignificantdifferencewasfound in terms of style, diet, usingnutritionalsupportproduct, beingnational, caringfordiet; significantdifferenceswerenoticed in terms of beingcontrolled of doping, category, level of education, andage of sports. Consequently, it can be saidthatattitudescores of elite wrestlersrelatedtotheuse of doping arehighandtheirattitude is positive.